THE EFFECTIVENESS OF DRILL METHOD IN ENHANCING ELEMENTARY SCHOOL STUDENTS’ VOCABULARY MASTERY - Ali, Indi Aulia; Sayid Ma’rifatulloh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
An essential part of learning a language is expanding one's vocabulary, which helps students comprehend and communicate concepts clearly. However, due to little practice and uninteresting teaching strategies, many primary school pupils still struggle to remember and use new words. For young students to enhance their language ability and build their memory, repetitive and systematic practice is thought to be crucial. The drill method is used here as a teaching strategy that prioritizes ongoing practice and reinforcement. This study used a one-group pretest-posttest methodology using a pre-experimental design 32 fifth-grade students of SDN Pelem 1 Pare in the academic year of 2025/2026. These two factors beforehand and afterwards the treatment process, Tests of vocabulary were used to gather information. The findings demonstrated an improvement in the pupils' vocabulary mastery as evidenced by the higher post-test scores when compared to the pre-test results. The student achievements before and after the therapy was given differed significantly, according to statistical analysis using a paired sample t-test these findings suggest that the drill method is effective in enhancing elementary school students’ vocabulary mastery.